(untitled) (World Bulletin of Public Health, 2024)
Carotid artery stenosis is a condition caused by the narrowing or constriction of the carotid arteries, which are responsible for supplying blood to the head. This condition often develops due to atherosclerosis and can lead to disruptions in blood circulation. Symptoms related to stenosis include headaches, dizziness, vision problems, and neurological signs. Hearing impairment may also occur as reduced blood flow to the inner ear can damage the auditory nerves, leading to hearing loss. Diagnostic methods include ultrasound, MRI, and angiography, which help assess the condition of the arteries. Treatment options range from medication and lifestyle changes to surgical procedures if necessary. Early detection and treatment of carotid artery stenosis are crucial for preserving hearing and improving overall health